Hubungan Antara Persahabatan Dengan Self Esteem - Putri, Anika; , Achmad Dwityanto, S.Psi, M.Si (2016)
Low self esteem is often connected with problems of mental disorders such as depression, anxiety, and learning problems. One of the factors that affect the self esteem is friendship. The aim of this research is to know the relation between friendship with self esteem, so the authors propose the hypothesis "there is a positive relationship between the friendship with self esteem".Subjects in this research is the psychology student, UMS 2013 that totalling 320. Sampling technique was incidental non random sampling that is anyone who by chance/incidental met of the researchers can be used as a sample, if a person is seen incidentally found it suitable as a data source. Measuring instrument which is used to reveal the research variables there are 2 kinds of measuring instrument, namely: (1) the scale of friendship, and (2) the scale of self esteem. Data analysis in this study uses the product moment correlation. Based on the analysis results, so that is obtained correlation between friendship with self esteem (r) amount of 0.425 with p = 0.000 which p < 0.01, this means there is a very significant positive relationship between friendship with self esteem. That is, the higher the friendship then the higher self esteem of the subject, and instead the lower friendship then the lower the self esteem of the subject anyway.The empirical mean of friendship variable amount of 104.69 with hypothetic mean amount of 90. So the empirical mean > hypothetic mean that illustrates that generally the subject matter has a high friendship. Furthermore the empirical mean of the self-esteem variable amount of 95.96 with hypothetic mean amount of 87.5. So the empirical mean > hypothetic mean that meaning in general subjects also have high self esteem. The role of friendship towards self esteem (SE) is 18% that meaning still present 82% that affects self esteem, for example: experience in the family, feedback in the performance, social comparison, and parents.